COT-18 Trends in Primary Brain Tumors in Kumamoto Prefecture with Declining Birthrate and Aging Population - Kumamoto Prefecture Brain Tumor Epidemiological Survey. (6th December 2021) - Shinojima, Naoki; Itoyama, Takashi; Mukasa, Akitake
Abstract: Backgrounds: The demographic characteristics of Kumamoto Prefecture are that there is little population movement and the total population remains constant at about 1.8 million, but in recent years the birthrate is declining and the population is aging. We have been conducting the Kumamoto Prefecture Brain Tumor Epidemiological Survey since 1989 in cooperation with neurosurgical institutions in the prefecture. In this study, we examined whether recent demographic changes have affected the incidence of primary brain tumors (BT). Methods: Patients with primary BT were collected annually from 44 institutions in Kumamoto Prefecture (as of 2020), and the number of incidences per 100, 000 population was calculated for each BT for each year, excluding patients living outside the prefecture and duplicate cases. Results: The total number of primary BT was 11441 (top 3: meningioma 40%, pituitary adenoma 17%, glioma 17%). Of 4261 men with primary BT, the top 3 were meningioma (27%), glioma (23.7%), and pituitary adenoma (18.4%)), and 7180 women (top 3: meningioma (47.7%), pituitary adenoma (16.2%), and glioma (12.9%)). The number of primary BT increased every year, and the incidence increased significantly when comparing 1989–2004 and 2005–2020 (13.6 vs. 25.0/100, 000, p<0.000001). Typical brain tumors (meningioma, pituitary adenoma, glioma, schwannoma, malignant lymphoma) also increased year by year, especially asymptomatic meningioma. The median age of asymptomatic meningiomas was significantly higher than that of symptomatic meningiomas (69 vs. 65 years, p<0.0001). Gliomas increased significantly in the later stages compared with the early stages in children (0–14 years) and the elderly (65 years and older). Conclusion: Our results suggest that an increase in the number of BT such as glioblastoma, which are more common in the elderly, as well as an increase in the number of opportunities for intracranial examinations in the aging of the population may be responsible for the increased incidence of primary BT.